Revisiting Humanism as guiding principle for education: An excursion into Waldorf Pedagogy - da Veiga, Marcelo (Educar em Revista, 2015)
This paper begins by highlight the growing relevance of Rudolf Steiner’s thinking within academic discourse. It then turns to a brief discussion of the consequences of physicalism and naturalism in education. In a third step, the concept of notional instrumentalism is presented as a possible way of overcoming the generally unfruitful debates about the comprehension of non-physical aspects of reality. All this serves finally to stress the importance of revisiting humanism as a potential guiding principle for education. Keywords: epistemology, education, humanism, Rudolf Steiner.